Chapter 13 Swedish teachers' digital competence - infrastructures for teaching and working - Godhe, Anna-Lena (Taylor & Francis, 2024)
Swedish teachers' digital competence refers to aspects of teaching as well as teachers' work in a broader context. In this chapter, 19 Swedish teachers' digital competence is analyzed as infrastructures for teaching and working, thereby setting digital competence in the context of teachers' work in and out of the classroom. This chapter contributes to an understanding of how contextual factors of teachers' digital competence relate to infrastructures for teaching and working and illuminates how contributing to teachers' digital competence is both an individual and a collective responsibility. The analysis highlights the challenges that teachers face and suggests how these can be understood and conceptualized in relation to individual and structural levels of schooling, and to teaching and working infrastructures.